Clinical and Imaging Findings of True Hemifacial Hyperplasia - Bansari A. Bhuta; Archana Yadav; Rajiv S. Desai; Shivani P. Bansal; Vipul V. Chemburkar; Prashant V. Dev (Case Reports in Dentistry)
Congenital hemifacial hyperplasia is a rare developmental disorder of unknown etiology, characterized by a marked unilateral facial asymmetry. It involves the hard (bones and teeth) and soft tissues of the face. We report an interesting case of true hemifacial hyperplasia in a 25-year-old male highlighting the clinical and computed tomography imaging findings.